2020
DOI: 10.26434/chemrxiv.11888925.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optical Control of Ca2+-Mediated Morphological Response in Glial Cells with Visible Light Using a Photocaged Kainoid

Abstract: A chemical probe (DECM-PhKA) was developed to study filopodia extension in glial cells with spatio-temporal control. Irradiating DECM-PhKA with blue light releases the neuroactive agonist phenylkainic acid with a half-lifetime of 61 seconds. The effect of rapid uncaging was demonstrated in U118-MG astrocyte cells. The agonist is released locally with high precision using an optic fiber to trigger calcium influx that leads to filopodia extension in the targeted cells. This chemical probe provides a new tool to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 43 publications
0
6
0
Order By: Relevance
“…We tested the effect of another kainoid known to bind selectively to KARs: phenylkainic acid (Ph-KA), to confirm further our observation. 18,19 Ph-KA caused the same response as KA (Fig. 4).…”
mentioning
confidence: 52%
See 1 more Smart Citation
“…We tested the effect of another kainoid known to bind selectively to KARs: phenylkainic acid (Ph-KA), to confirm further our observation. 18,19 Ph-KA caused the same response as KA (Fig. 4).…”
mentioning
confidence: 52%
“…Based on our practical synthesis of kainoid analogs, we designed a C4-heteroaryl kainoid that was expected to be more potent than its parent natural product kainic acid. 17,19,20 Our previous SAR analysis 12 suggested that C4-aryl kainoids are highly potent KAR agonists, mostly due to the C4 substituent participating in π-π stacking with a key phenol side chain within the binding pocket (Tyr448, Figure 3). Aminooxazolyl kainoid 1 was selected for two main reasons: (1) its electron-deficient quadrupole would complement and enhance π-π stacking interactions with Tyr488, and (2) the 2amino substituent would allow easy attachment of different molecular cargo to create new chemical biology tools (e.g., fluorescent tags, biotin, photoswitch, etc.…”
mentioning
confidence: 99%
“…As described above, we recently reported that glutamate receptors sensitive to kainic acid are involved in filopodiagenesis. Intriguingly, we also found that Ca V 1.2 voltage-gated calcium ion channels may also participate in filopodiagenesis in astrocytoma cells [ 64 , 65 , 81 , 82 ].…”
Section: Calcium Influx In Astrocytomamentioning
confidence: 93%
“…Astrocytes and astrocytoma cells also express kainic acid receptors (KARs), but their function remains largely unexplored [ 23 , 58 , 59 ]. Since astrocytoma progression is known to be affected by perturbed glutamate homeostasis [ 60 , 61 , 62 , 63 ], our lab investigated the relationship between the glutamate stimulation of astrocytoma cells and their aberrant morphology [ 64 , 65 ]. Glutamate was found to trigger the rapid extension of processes in astrocytoma cells (as observed in their parent astrocytes).…”
Section: Glutamate Signalingmentioning
confidence: 99%
“…Yet, three decades after introducing the tripartite synapse model (where an astrocyte makes a direct contact with the pre-and post-synaptic neurons) [18], the molecular mechanisms of astrocytic glutamate signaling are still under investigation [19][20][21]. Following the first report by Cornel-Bell et al showing that glutamate initiates a calcium-dependent response of cultured astrocytes [15,16], several groups have examined how astrocytes respond to neuronal activity and neurotransmitter release in vivo [22][23][24][25][26][27][28][29]. In line with the mounting evidence that calcium-permeable or calcium-releasing glutamate receptors may be involved [19,27,29], we recently found that LTCCs participate to the glutamate-induced response in a model astrocyte cell U118-MG [26].…”
Section: Introductionmentioning
confidence: 99%